Corticosteroid Regulation of Synaptic Plasticity in the Hippocampus. (2010) - Maggio, Nicola; Segal, Menahem
Abstract : Stress, via release of steroid hormones, has been shown to affect several cellular functions in the brain, including synaptic receptors and ion channels. As such, corticosteroids were reported to modulate plasticity, expressed as long-term changes in reactivity to afferent stimulation. The classical view of the effects of stress on synaptic plasticity and cognitive functions assumes an inverted U-shape curve, such that a low stress level facilitates and a high stress level (i.e., corticosterone levels) impairs cognitive functions. This universal view has been challenged recently in a series of studies that show that stress and corticosterone have immediate and opposite effects on the ability to express long-term potentiation (LTP) in the dorsal and ventral sectors of the hippocampus. This differential role of stress may be related to the different functions associated with these sectors of the hippocampus. Herein, we review the known effects of stress hormones on cellular functions and outline the role of molecular mechanisms in stress-related global functions of the hippocampus.